2010
DOI: 10.1523/jneurosci.2524-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Rats Markedly Escalate Their Intake and Show a Persistent Susceptibility to Reinstatement Only When Cocaine Is Injected Rapidly

Abstract: When drugs enter the brain rapidly, liability for addiction is increased, but why this is the case is not well understood. Here we examined the influence of varying the speed of intravenous cocaine delivery on self-administration behavior in rats given limited or extended opportunity to take drug. The speed of cocaine delivery had no effect on self-administration behavior when rats were given only 1 h each day to take cocaine. When given sixfold more time to take cocaine, rats that received cocaine rapidly (5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 60 publications
(83 reference statements)
6
63
1
Order By: Relevance
“…In rodents, different rates of cocaine delivery affect its addictive liability-drugs reaching the brain rapidly are more addictive than those that reach the brain slowly (Oldendorf, 1992;Samaha and Robinson, 2005;Wakabayashi et al, 2010). Similarly, in humans, the more rapidly cocaine (Volkow et al, 2000) or methylphenidate (Volkow et al, 2002) enters the brain, the greater the reported 'high'.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, different rates of cocaine delivery affect its addictive liability-drugs reaching the brain rapidly are more addictive than those that reach the brain slowly (Oldendorf, 1992;Samaha and Robinson, 2005;Wakabayashi et al, 2010). Similarly, in humans, the more rapidly cocaine (Volkow et al, 2000) or methylphenidate (Volkow et al, 2002) enters the brain, the greater the reported 'high'.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with increased cocaine-induced reinstatement only in rats that have had long (6 h), but not short (1 h), daily access to the drug (Crombag et al, 2008;Wakabayashi et al, 2010). In addition, fast delivery rate is necessary to observe high frequency use (escalation) in the 6-h rats (Wakabayashi et al, 2010), supporting that the two factors, ie, high reinstatement and high frequency use, are related. Finally, protocols leading to repeated transiently high plasma levels of cocaine increase motivation for cocaine, supporting that frequency of cocaine use can impact its psychopharmacological consequences (Zimmer et al, 2012).…”
Section: High and Low Frequency Rats: Distinct Pharmacological Profilesmentioning
confidence: 95%
“…Shortening the time to peak cocaine brain levels (through narrow manipulation of the rate of infusion from 5 to 90 s), without altering the peak level achieved, provokes sensitization of the psychomotor and reinforcing effects of psychostimulants and produces specific and relevant neurobiological adaptations Liu et al, 2005aLiu et al, , 2005bSamaha and Robinson, 2005;Samaha et al, 2002Samaha et al, , 2004. However, it is associated with increased cocaine-induced reinstatement only in rats that have had long (6 h), but not short (1 h), daily access to the drug (Crombag et al, 2008;Wakabayashi et al, 2010). In addition, fast delivery rate is necessary to observe high frequency use (escalation) in the 6-h rats (Wakabayashi et al, 2010), supporting that the two factors, ie, high reinstatement and high frequency use, are related.…”
Section: High and Low Frequency Rats: Distinct Pharmacological Profilesmentioning
confidence: 99%
“…Mechanistically, addiction is hypothesized to hijack healthy learning, memory, and motivation circuits, altering them to focus on the procurement and consumption of the drug of abuse (Hyman, 2005). The difference between performance enhancement and addiction, with respect to stimulants, prominently depends on two closely related factors: dose and route of administration (Boutrel and Koob, 2004;Volkow et al, 2005;Ferrario et al, 2008;Fowler et al, 2008;Wakabayashi et al, 2010). Specifically, high doses and rapid routes of administration seem integral to the development of addiction.…”
Section: Introductionmentioning
confidence: 99%